Jawabanmu

2014-09-07T11:40:00+07:00
x^2x^4 = x^{(2+4)}=x^6
\frac{x^2}{x^4} =x^{(2-4)}=x^{-2}=  \frac{1}{x^2}

a. \frac{32p^2q^3r^4}{(2p^3q^2)(8pq^4r^3)}

= \frac{32p^2q^3r^4}{2.8.p^3.p.q^2.q^4.r^3}

= \frac{32p^2q^3r^4}{2.8. p^{(3+1)}.q^{(2+4)}.r^3}   

=\frac{32p^2q^3r^4}{16. p^{4}.q^{6}.r^3}

= \frac{32}{16} . \frac{p^2}{p^4} . \frac{q^3}{q^6} . \frac{r^4}{r^3}

=2p^{(2-4)}q^{(3-6)}r^{(4-3)}

=2p^{-2}q^{-3}r

=\frac{2r}{p^2q^3}

b. 2a^2b^2c^3+3ab^2c^3-4a^2b^3c^4
pertama mengeluarkan a
=a(2ab^2c^3+3b^2c^3-4ab^3c^4)
kedua mengeluarkan b
=ab^2(2ac^3+3c^3-4abc^4)
ketiga mengeluarkan c
=ab^2c^3(2a+3-4abc)
2014-09-07T11:50:52+07:00